2017
DOI: 10.1002/ange.201612093
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Channel Specifically Inserts into the Lipid Bilayer of Gram‐Positive Bacteria but not that of Mammalian Erythrocytes

Abstract: As eries of tubular molecules with different lengths have been synthesized by attaching Trp-incorporated peptides to the pillar[5]arene backbone.The tubular molecules are able to insert into the lipid bilayer to form unimolecular transmembrane channels.One of the channels has been revealed to specifically insert into the bilayer of the Gram-positive bacteria. In contrast, this channel cannot insert into the membranes of the mammalian rat erythrocytes even at the high concentration of 100 mm.Itwas further demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 46 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…8 For example, a peripheral acetylated mannosyl moieties-functionalized pillar [5]arene showed antiadhesion activity against uropathogenic Escherichia coli. 9 Not only pillar [5]arenes with incorpo-rated peptides, 10 phosphonium or ammonium, 11 guanidinium groups 12 but zwitterionic pillar [5]arenes 8 have also shown their unique antibacterial or antibiofilm activities. These results indicated that pillararene might be a useful scaffold for the construction of new antibacterial agents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8 For example, a peripheral acetylated mannosyl moieties-functionalized pillar [5]arene showed antiadhesion activity against uropathogenic Escherichia coli. 9 Not only pillar [5]arenes with incorpo-rated peptides, 10 phosphonium or ammonium, 11 guanidinium groups 12 but zwitterionic pillar [5]arenes 8 have also shown their unique antibacterial or antibiofilm activities. These results indicated that pillararene might be a useful scaffold for the construction of new antibacterial agents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Actually, since the mechanism of action does not rely on metabolic pathways, the tube proved active and selective for Methicillin-resistant Staphylococcus aureus (MRSA) with very low toxicity for mammalian cells. [60] Despite anionophores have been less studied than cationophores, the development of small-molecule anion transporters has increased in the last years. [61] Tomich and co-workers focused on the use of short peptides as chloride channels.…”
mentioning
confidence: 99%